Academic Supervision as a Strategy for Improving Teaching and Learning Quality - Lalu Sugiar; Sukirman Sukirman; Syamsu Sanusi (Har Press Indonesia, 2024)
This study examines the implementation of academic supervision as a strategy to improve teaching and learning quality at MTs Negeri Palopo. Academic supervision systematically involves classroom observations, constructive feedback, and collaborative discussions between supervisors and teachers to enhance professional development and align teaching practices with curriculum standards. The research identifies strong collaboration between supervisors and teachers, proactive school leadership, and adequate resource provision as key factors contributing to academic supervision's success. Teachers are actively involved in decision-making and benefit from evidence-based feedback derived from student performance data. Efforts to improve teaching and learning quality at MTs Negeri Palopo include teacher professional development programs, curriculum refinement, classroom management guidance, and data-driven interventions. These initiatives are facilitated through internal forums, external training, and supervisory support, enabling teachers to adopt innovative instructional practices and address classroom challenges effectively. Despite these successes, challenges such as limited time for supervision, resistance to feedback, and occasional communication gaps hinder the full potential of academic supervision. The findings suggest that addressing these challenges through improved time management, fostering openness to feedback, and enhancing communication strategies can amplify the positive impact of supervision on teaching quality and student outcomes. By optimizing academic supervision practices, MTs Negeri Palopo can continue to deliver high-quality education and serve as a model for similar educational institutions.